A three-step approach to post-fire mortality modelling in maritime pine (Pinus pinaster Ait.) stands for enhanced forest planning in Portugal - Garcia-Gonzalo, J. (2019)
Maritime pine (Pinus pinaster Ait) is a very important timber-producing species in Portugal with a yield of ~67.1 million m3 year21. It covers ~22.6 per cent of the forest area (710.6 × 103 ha). Fire is the most significant threat to maritime pine plantations. This paper discusses research aiming at the development of post-fire mortality models for P. pinaster Ait stands in Portugal that can be used for enhanced integration of forest and fire management planning activities. Post-fire mortality was modelled using biometric and fire data from 2005/2006 National Forest Inventory plots and other sample plots within 2006–2008 fire perimeters. A three-step modelling strategy based on logistic regression methods was used. Firstly, the probability of mortality to occur after a wildfire in a stand is predicted and secondly, the degree of mortality caused by a wildfire on stands where mortality occurs is quantified. Thirdly, mortality is distributed among trees. The models are based on easily measurable tree characteristics so that forest managers may predict post-fire mortality based on forest structure. The models show that relative mortality decreases when average d.b.h. increases, while slope and tree size diversity increase the mortality